Tes Standar dan Tes Buatan Guru - Sa'baniah Sa'baniah; Nur Hasyikin; Eka Widyanti (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Education is very important for human life so it must be fulfilled and carried out to improve the quality of human life. Therefore, to see the results or progress of the education, whether the results are good or bad. Evaluation and assessment must be carried out by an educational institution, but this evaluation and assessment has an administration that must be followed by an educational institution. This article explains clearly the administration of evaluation and assessment in education including definition, objectives, functions, space, scope and targets.